Management Accounting Information System Design For Financial Reporting - Wahyu Setyawan; Surya Prasetya Trihatmaja; Reza Juang Riansyah (Program Pascasarjana STIE Amkop Makassar, 2023)
By developing an Accounting Information System for Financial Reporting in accordance with the Standards Accountancy Finance BUMDes, this study seeks to understand how a BUMDes generates financial reports and to address issues that arise when carrying out reporting finances in BUMDes Forward Sentosa Village central Lampung. Study In this qualitative descriptive study, information was gathered through interviews, observations, document reviews, and literature reviews. Data gathered from observation and interview processes is then further processed, analysed, and reported on to create systems for accounting, analysing human resources, developing computerised systems, and terminating withdrawal conclusions. Additionally, waterfalls are used in the SDLC approach of system information, accounting, reporting, and finance design. Keywords: BUMDes; Report Finance; Design; Information Systems Accountancy; SAK Entity private